Theater and life skills in six university students - Arellano Montoya, Rosa Elena (2024)
Through a narrative research using guided interviews, photographic records and participant observation with members of the Theater Company of the University Center of the South of the University of Guadalajara (CTC) we analyze some of life skills obtained in six female members of the CTC who participated during two generations (the first starting in June 2011 and the second, starting in February 2014). The results showed that the student- actresses managed to develop their skills of self-knowledge, self-esteem, decision-making, creative thinking, critical thinking, empathy, management of emotions and feelings, management of tensions and stress, assertive communication, interpersonal relationships, and management of problems and conflicts. Likewise, the participants in the process defined their life goals, discovered their different abilities and strengths, created strategies for managing uncertainty, built a sense of belonging and a favorable transformation of their social environment. It was concluded that the theatrical performance process of the CUSur Theater Company through meaningful experiences and learning in a playful, dynamic, interactive and tolerant space, served as a pedagogical strategy that allowed its members to obtain different artistic skills; and the development of cognitive, emotional and social skills, which have a favorable impact on their quality of life.